Quality of Life Philosophy V. Seizing the Meaning of Life and Becoming Well Again - Søren Ventegodt; Niels Jørgen Andersen; Joav Merrick (The Scientific World Journal)
This paper presents a positive philosophy of life developed to support and inspire patients to take more responsibility for their own lives and to draw more efficiently on their known or hidden resources. The idea is that everybody can become wiser, use themselves better, and thus improve quality of life, subjective health, and the ability to function.To be responsible means to see yourself as the cause of your own existence and state of being. To be the one who forms your own life to your liking, so that others do not shape it in the way they prefer to see you. Seen this way, taking responsibility in practice is one of the most difficult things to do. One of the greatest and most difficult things to do in this context is to be able to love. To be the one who loves, instead of being the one who demands love, care, awareness, respect, and acceptance from somebody else.Since almost all of us have had parents who maybe loved us too little and mostly conditionally, we all harbor a deep yearning to be loved as we are, unconditionally. A lot of our energy is spent trying to find recognition and acceptance, more or less as we did as children from our parents, who created the framework and defined the rules of the game. But today, reality is different. We have grown up and now life is about shaping our own existence. So we must be the ones who love. This is what responsibility is all about. Taking responsibility is, quite literally, moving the barriers in our lives inside ourselves. Taking responsibility for life means that you are willing to see that the real barriers are not all these external ones, but something that can be found within yourself. Of course there is an outside world that cannot be easily shaped according to your dreams. But a responsible point of view is that although it is difficult, the problem is not impossible; it is your real challenge and task. If there is something you really want, you can achieve it, but whether it happens depends on your wholehearted, goal-oriented, and continuous attempts. This paper describes the philosophy about seizing the meaning of life and becoming well again, even when there is little time left.